Epigenetic Regulation of NRF2/KEAP1 by Phytochemicals - Shamee Bhattacharjee; Roderick H. Dashwood (MDPI AG, 2020)
Epigenetics has provided a new dimension to our understanding of nuclear factor erythroid 2-related factor 2/Kelch-like ECH-associated protein 1 (human NRF2/KEAP1 and murine Nrf2/Keap1) signaling. Unlike the genetic changes affecting DNA sequence, the reversible nature of epigenetic alterations provides an attractive avenue for cancer interception. Thus, targeting epigenetic mechanisms in the corresponding signaling networks represents an enticing strategy for therapeutic intervention with dietary phytochemicals acting at transcriptional, post-transcriptional, and post-translational levels. This regulation involves the interplay of histone modifications and DNA methylation states in the human NFE2L2/KEAP1 and murine Nfe2l2/Keap1 genes, acetylation of lysine residues in NRF2 and Nrf2, interaction with bromodomain and extraterminal domain (BET) acetyl "reader" proteins, and non-coding RNAs such as microRNA (miRNA) and long non-coding RNA (lncRNA). Phytochemicals documented to modulate NRF2 signaling act by reversing hypermethylated states in the CpG islands of NFE2L2 or Nfe2l2, via the inhibition of DNA methyltransferases (DNMTs) and histone deacetylases (HDACs), through the induction of ten-eleven translocation (TET) enzymes, or by inducing miRNA to target the 3'-UTR of the corresponding mRNA transcripts. To date, fewer than twenty phytochemicals have been reported as NRF2 epigenetic modifiers, including curcumin, sulforaphane, resveratrol, reserpine, and ursolic acid. This opens avenues for exploring additional dietary phytochemicals that regulate the human epigenome, and the potential for novel strategies to target NRF2 signaling with a view to beneficial interception of cancer and other chronic diseases.